Mutation analysis in patients of Mediterranean descent with Wilson disease: identification of 19 novel mutations - Loudianos, G. (BMJ Group, 1999)
In this study, we report further results of mutation analysis of the ATP7B gene in Wilson disease (WD) patients of Mediterranean origin. A total of 136 WD chromosomes, 73 of which were of Italian, 43 of Turkish, 18 of Sardinian, and two of Spanish origin, were analysed and the mutation characterised in 84.5% of them. We found 50 different mutations of which 19 are novel, including three nonsense, one frameshift, and 15 missense mutations. The mutations detected were rare and mostly found in the compound heterozygous state together with other mutations and only rarely in homozygosity. Most of these mutations lie in the transmembrane and ATP binding loop regions. These data expand our knowledge of both the structure-function relationships of the WD protein and the molecular pathology of WD, thus improving our capability of prevention and genetic counselling.   Keywords: Wilson disease; mutation; ATP7B; compound heterozygote